Microstructure and Mechanical Properties of High Velocity Oxygen Fuel (HVOF) Sprayed Nickel Powder Coating on Welding Regions of Aluminum Alloy AA5754 and DP600 Welded Steel Plates with the Friction Stir Spot Welding Process - (:unkn) unknown (My University, 2016)
Bu çalışmada, sürtünme karıştırma nokta kaynağının yüksek hızlı oksijen yakıtlı alev toz püskürtme yöntemiyle nikel kaplanmış malzemelerdeki mikroyapı ve mekanik özelliklerinin incelenmesi amaçlanmıştır. AA5754 alüminyum alaşımı kaynak yüzeyleri HVOF metodu kullanılarak 200 µm kalınlığında nikel ile kaplanmıştır. Sürtünme karıştırma nokta kaynağı takımı sıcak işlem çeliğinden tasarlanmış ve imal edilmiştir. Metalografik numuneler abrasif su jeti ile kaynaklı parçalardan kesilmiştir. Numuneler Metalografik olarak hazırlanmış ve temel metal, kaynak bölgesi ve ısıdan etkilenen bölge Vickers sertliğinde ölçülmüştür. Numunelerin mikro yapısı taramalı elektron mikroskobu, EDS analizi ve optik mikroskop görüntüleme ile incelenmiştir. Deneysel çalışma sonuçları, mikroyapı ve kaynaklı birleştirmenin mekanik özellikleri analizi için yorumlanmıştır.

In this study, it is aimed to investigate microstructural and mechanical properties of friction stir spot welding joints coated with nickel powder by using high velocity oxygen fuel method HVOF. The welding surfaces of AA5754 alloy was coated with nickel powder with a thickness of 200 µm by using HVOF. Friction Stir spot welding tool was designed and manufactured from hot worked tool steel by machining. Metallographic specimens were cut from welding samples by using abrasive water jet. Specimens were metallo graphically prepared and Vickers hardness of base metal, welding zone and heat affected zones were measured. Microstructure of the specimens investigated by using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS) and optical microscope analysis. The results of experimental studies were interpreted in order to analyze microstructural and mechanical properties of welding joints.
Yüksek Hızlı Oksijen Yakıtlı Alev Toz Püskürtme Yöntemiyle Nikel Kaplanmış AA5754 Alüminyum Alaşımı ve DP600 Galvanizli Çeliğin Sürtünme Karıştırma Nokta Kaynağı ile Birleştirilmesinde Mikroyapı ve Mekanik Özelliklerin İncelenmesi
Keywords: Mimarlık